Indonezyjskie i polskie idiomy – w poszukiwaniu ekwiwalentów tłumaczeniowych - Wiatrowski, Przemysław (Poznańskie Spotkania Językoznawcze, 2015)
This paper focuses on Indonesian and Polish idioms analysed from an inter-lingual standpoint, with particular emphasis on their image components. The research material comes from general and specialized (phraseological) dictionaries of both languages. The objective is to assign Polish translation equivalents to selected Indonesian idioms. As no text corpora or translation series are available for Indonesian and Polish, the investigation is limited to systemic (lexicological) equivalence. The analysis of the Polish equivalents of Indonesian idioms covers stable set phrases which carry the same image, idioms which carry an analogous image, and idioms with identical meaning which carry a different image. Also considered are false equivalents (pseudo-equivalents).